Artificial Intelligence in Film and Television Production: Idea Generation and Post-Production - Li, Kang (Malikussaleh University, Aceh, Indonesia, 2025)
This paper takes the impact of artificial intelligence on film and television art creation as the topic, from the creative generation of film and television art creation and post-production, two aspects of the impact of artificial intelligence on film and television production. The impact of artificial intelligence on film and television production for a more in-depth discussion and research, combined with examples of research and analysis, the use of science and technology point of view theory of film and television art creation in the new era of the artistic impact of the presentation of a specific description. Through the study, artificial intelligence plays a pivotal role in the process of film and television production, from pre-planning to script writing to later video editing and special effects production. The successful use of artificial intelligence in the field of film and television art creation has a great impact on the overall value chain involving the film and television industry, which is of great social significance.